Solar Power System Design Applications for Pool Water Pump Operation at Tourist Accomodation - I Gusti Agung Bagus Wirajati; I Dewa Made Cipta Santosa; Ida Bagus Aditya Jaya Pramana; I Putu Gede Suka Haryasa; Ida Ayu Gede Bintang Madrini (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
Utilization of solar energy in Indonesia has begun to bloom. This is due to the fact that Indonesia is located at the equator where the sun is exposed all year round and is a very environmentally friendly energy. Based on this, solar energy is used as an option to meet electricity needs by using a photovoltaic (PV) system. The use of a photovoltaic system as a power provider to operate a pool water pump at a villa in Bali is an example of the application of a photovoltaic system. In this study, A Seri and Parallel photovoltaic arrays were used with a panel system that was integrated with PLN electricity. The angle of inclination and direction of placement chosen in this study is 15° with facing north, which refers to research that, has been done previously. PV designs and a series of control panels that can be accessed via the internet will be described as well. The aim in this research is investigate how photovoltaic design used as a solar power plant which applied to the module can be runing the pool water pump in the villa or tourist accommodation.